Understanding of the Kinetic Stability of cis‐ Isomer of Azobenzenes through Kinetic and Computational Studies. Issue 44 (24th November 2020) - Das, Dhiraj; Yadav, Manish K.; Singla, Labhini; Kumar, Atul; Karanam, Maheswararao; Dev, Sagarika; Choudhury, Angshuman R.
Abstract: A library of halogen‐substituted azobenzenes (ABs) have been synthesized and structurally characterized by single crystal X‐ray diffraction technique. Azobenzenes studied herein display fast photo switching properties. Kinetics of cis‐ → trans‐ isomerization has been studied using UV‐VIS spectroscopy and the rate constant for this transformation were determined. Optimization of probable conformers of the cis‐ isomer and the corresponding transition state (TS) were carried out to determine the energy of activation. The Time‐Dependent Density Functional Theory (TD‐DFT) calculations were also performed to gain insight into the photo‐isomerization. Our results indicate that the fluorinated compounds display better kinetic stability of the cis‐ isomer compared to the corresponding chloro and bromo analogues. Abstract : The kinetic stability of 15 halogenated azobenzenes has been analysed experimentally using UV‐VIS spectroscopy and using abinitio calculations. Most stable conformers of cis‐, trans‐ and the TS were identified using IRC calculations. Fluorinated analogues remained partially unconverted to trans‐ form from their respective cis‐ form up to after 4 days. Fluorinated azobenzenes demonstrated better kinetic stability over chloro and bromo analogues.